Óleo essencial de Lippia Alba (mill.) n. e. brown: variação sazonal, atividades antimicrobiana, antioxidante e sua aplicação em uma eficiente formulação para inibição de micro-organismos patogênicos - SILVA JÚNIOR, Antônio Quaresma da (Universidade Federal do Oeste do Pará, 2021)
Many studies have reported a large variation of the chemical constituents of the essential oil (EO) of Lippia alba (Mill.) N.E. Brown, with seasonality, genetic and environmental factors being the main responsible for these differences. Thus, the objective of this work was to evaluate the influence of seasonality and time of harvest on the yield, chemical composition and antimicrobial and antioxidant activities of L. alba essential oil grown in Santarém, Pará, Brazil, in addition to developing a topical use formulation containing EO with antimicrobial activity. Leaves of L. alba were collected during the rainy season and the dry season at 8 a.m, 12 p.m and 5 p.m in 2014 and during the period from January 2016 to January 2017. Climatic parameters were monitored throughout the harvest period. EO was obtained by hydrodistillation and its chemical components were analyzed by gas chromatography coupled to mass spectrometry (GC-MS). The formulation of topical use was prepared with the incorporation of 10% of the EO to an anionic base of the type Lanette® and submitted to evaluation of its stability. The antibacterial activity against S. epidermidis (CCCD S010) of the formulation and EO was performed by disc diffusion agar and broth microdilution methods. For the antioxidant activity of EO, was used the DPPH radical sequestration method. The main chemical constituents of EO (above 2%) were submitted to multivariate statistical analysis (PCA, Principal Component Analysis, HCA, Hierarchical Cluster Analysis). The average yield of EO ranged from 2.2 to 4.3% in 2014, with the highest percentage for the rainy season (in March), whereas in 2016 it varied from 1.6 to 4.5%, with significant variation due to seasonality. The HCA and PCA analyzes confirmed the influence of seasonality on the chemical composition of L. alba EO. Rainfall and solar radiation may be the main factors that contributed to the variation of some chemical components of EO during the months of the year. However, the major chemical compound of the species is always citral, regardless of the seasonal period and time of harvest, which characterizes its chemotype. The formulated product containing the oil remained about 45% citral and showed stability at temperatures up to 25 °C. In the centrifugation test no changes were observed regarding homogeneity, indicating a good compatibility between the base and the EO. The inhibition halo against S. epidermidis was 16 ± 1.73 mm (at 5 °C) and 7.16 ± 0.28 mm (at 25 °C) for the formulation and > 45 mm for pure EO in both periods. It was observed higher EO effectiveness in the rainy season with MIC of 1.25 μl/ml and 2.5 μl/ml in the dry season. In the antioxidant activity, the samples presented low antioxidant capacity, with percentages of DPPH inhibition varying from 0.97 ± 0.16% to 2.87 ± 0.68%, without significant influence of seasonality. According to the results, the harvest period influenced the yield, chemical composition and antimicrobial activity of L. alba EO. The formulation containing EO presented a good stability and has considerable antimicrobial action against S. epidermidis, which stimulates the continuity of the studies.